FDI, exports and labor productivity of Vietnamese enterprises with different levels of capital and labor-intensity - Dao, Vu Phuong Linh; Nguyen, Thi Le Hang; Nguyen, Ngoc Tien (Nurture, 2024)
Purpose: This study aims to examine the differential impact of two channels of international technology transfer, namely foreign direct investment (FDI) and exports on the labor productivity of firms in Vietnam with varying levels of capital-intensity and labor-intensity. This study aims to provide empirical evidence for policies that enhance Vietnamese firms' labor productivity. Design/Methodology/Approach: This study uses panel data and employs a fixed effects model (FEM) and a random effects model (REM) to examine the impact of FDI and the exports on labor productivity of both large firms, small and medium-sized enterprises (SMEs) using firm-level data from Vietnam in 2015 and 2016. Findings: This study finds evidence that FDI has a positive impact on firm-level labor productivity while exports do not significantly affect labor productivity for labor-intensive industries (represented by the garment industry). Conversely, for capital intensive industries and firms operating in these industries (represented by the metal casting industry), FDI appears ineffective in improving labor productivity. Still, exports are an important factor influencing labor productivity for these firms. Conclusion: Firms operating in industries with different labor and capital intensity require different strategies to enhance labor productivity. Appropriate policies need to be implemented to achieve the desired outcomes depending on the characteristics of each firm. Research Limitations and Implications: This study only focuses on studying the relationship between FDI, exports and labor productivity with different capital levels and labor-intensity not mentioning the business field of the enterprise. Practical Implications: The new findings of the study make a great contribution to promulgating policies to attract FDI, promote exports and increase labor productivity at enterprises in Vietnam. Contribution to the Literature: The relationship between FDI, exports and labor productivity with different levels of capital and labor-intensity according to different business fields of the enterprise was examined.